ABOUT THE FUTURISTIC CITY OF NEOM IN SAUDI ARABIA - E. S. Biryukov (Вестник университета)
The applied aspect of the policy of the Kingdom of Saudi Arabia (KSA) aimed at economic diversification - the construction of the city of the future Neom - is considered. The purpose of the research is to analyze the possibilities of the Kingdom for the implementation of the project. The methodological base consists of studying the existing experience of the KSA on the construction of cities, its comparative analysis with the policy of other Arabian monarchies, and forecasting the prospects of the project on this basis. It was revealed that Saudi Arabia has accumulated a wealth of experience in this field. At the same time it is shown that at the beginning of the XXI century many announced projects were not implemented. The main risks will be the amount of necessary funds, namely 500 billion dollars; the unprecedented nature of the project in terms of the level of technology used; political situation. The results of the research can be used to assess the prospects for the development of the KSA and the directions of interaction be-tween Russian and Saudi companies.